Development of Learning Material for the Livestock Production System at the Beef Cattle Farmers - Ahmad Romadhoni Surya Putra; Fransiskus Trisakti Haryadi; Budi Guntoro; Endang Sulastri; Siti Andarwati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
The activity aimed to arrange the learning materials for farmer based on the cattle production system. The learning materials or curriculum is developed based on system theory perspective. In the system theory, there are two approaches which are hard system and soft system. The hard system refers to a quantitative perspective with rigid indicators such as technology implementation, productivity, and efficiency. Meanwhile, the soft system considers problem-solving based on the level of understanding, attitude and participation, teamwork, and motivation. This community services focused on applying soft system approach to arrange learning materials through farmer participation. The Participatory Rural Appraisal (PRA) technique was conducted to stimulate farmers to identify their production problems and to prioritize the problem solving for learning materials. This article concluded that cattle farmers were able to identify and to prioritize the problem better through PRA stages.